REUSE STRATEGIES OF DEAD SHOPPING MALLS - Sariakcali, Ali Bugra; Manisa, Kunter (INT ORGANIZATION CENTER ACAD RESEARCH, 2018)
Shopping is one of the most fundamental and general activities of mankind. The need for shopping areas took place in the urban squares of medieval cities and antiquity. As time progresses, it began to shift out of the city center with the great passages and stores that emerge in the 19th century. Victor Gruen's invention Southdale Center, separated the urban fabric and shopping activity from each other and became the first completely enclosed and air conditioned mall in the history. After Southdale Center, shopping centers differentiated in scale, quality, in terms of space and organization and their numbers rapidly increased. Nowadays, todays shopping mall is more than providing community's demands; they turn into the urban focal points that reflect the socio-cultural characteristics of the society with the sporting practices, cultural activities, entertainment and recreation areas, restaurants, cafes in them. Since 1990's, changes in socio economic, over-retailing, tough competition, widening e-commerce due to the development of technology, mistaken architectural, locational and urban planning decisions influenced to the shopping malls and they began to lose their functions and economic vitality in developed countries. Older shopping malls fails as newer shopping venues are built with better qualities, easier accessibility and transportation and latest design trends. Declined shopping malls begins to become non-functional areas and brings physical and economic depression not for just themselves; they also sinks nearby of the their built environment and creates dead spaces. The shopping malls sites that completed their functional lifetime ensure available options for revitalize and redevelopment opportunities. Therefore, various redevelopment and adaptive reuse projects have begun to implement for the dead malls. Within the scope of this study, reused shopping malls examples in USA and Turkey reviewed and findings from the projects, schematized by diagrams.
Keywords: Shopping Malls; Adaptive Reuse; Sustainability; Turkey; USA; Education & Educational Research; Social Sciences - Other Topics